Optimal Capacity Planning of Power to Hydrogen in Integrated Electricity–Hydrogen–Gas Energy Systems Considering Flexibility and Hydrogen Injection - Wang, Jinpeng; Zeng, Pingliang; Li, Yalou; Liu, Jia (Frontiers in Energy Research, 2022)
Power-to-hydrogen (P2H) plays an important role in the low carbon renewable dominated energy systems. By blending green hydrogen produced from renewable power into the natural gas pipelines, it is possible to help integrate large scale intermittent generation and smoothing the variability of renewable power output through the interconnection of the natural gas network, hydrogen energy network, and the electric network. A two-stage stochastic mixed-integer nonlinear planning framework for P2H sizing and siting is proposed in this paper, considering system flexibility requirements. The problem is then reduced to a mixed integer second order cone (MISOC) model through convex transformation techniques in order to reduce the computation burden. Then, a distributed algorithm based on Bender’s decomposition is applied to obtain the optimal solution. Simulation results carried out on two cases show the validity of the proposed MISOC model. Numerical tests demonstrated that planned P2H reduced CO2 emissions, enhanced system flexibility, and increased the consumption of renewable energy.